DIGITAL CONTENTS FOR ENHANCING THE COMMUNICATION OF MUSEUM EXHIBITION: THE PERVIVAL PROJECT - L. L. Micoli; S. Gonizzi Barsanti; G. Caruso; G. Guidi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The PERVIVAL project aims at developing an interactive system with the preliminary function of explaining a complex museum collection in a simple and immediate way and allowing the visitor to better understand the museum collection he is about to see. In particular, the interactive system aims at enhancing the understanding of the collections of funeral furnishings of Egyptians, which are characterized by a multiplicity of objects of rich symbolism and connected to each other through complex funeral rituals. The idea is to explain the religious creed of ancient Egyptians through the objects placed in the tomb, having in this way a double benefit: enlightening the rituals and placing the objects back in their primary function. In this way, the knowledge of the visitor is not only enlarged through the description of something that is described on papyruses or inscriptions (hence, not comprehensible) but also the proper function of every single object will be explained through the connection among them, as a function of amulets or goods necessary to travel through the World of the Dead. The connection between the different objects allows a much greater understanding of the exposed collection that would be perceived in this way not as a set of single isolated pieces, but as a harmonious set of complementary elements between they represent a specific historical-cultural context.